The reality of using the learning styles of multiplication and division from the third-grade teachers in Jordan, and its relationship to the quality of distance learning from their point of view - Hawalta, Raja' Yousef (Journal of Educational and Psychological Sciences, 2020)
The research aimed for identifying the extent of the reality of the use of mathematics teachers for the third grade of learning styles in teaching multiplication and division tables and its impact on the quality of distance learning from their point of view. The sample consisted of (250) male and female primary school teachers, and the sample was randomly chosen. The questionnaire was distributed electronically after confirming its validity and reliability. The results of the research indicated that the increase in the efficiency of the teacher in using learning styles in teaching the multiplication and division tables for the third grade by one unit will lead to an increase in the quality of distance learning by (0.714). There are also statistically significant differences among the arithmetic averages of mathematics teachers ’responses in Marka basic schools because of the importance of applying learning styles used in distance learning due to experience variable. While there are no statistically significant differences between the averages of mathematics teachers ’responses in Marka basic schools because of the importance of applying learning styles used in distance learning due to the educational qualification. The researcher recommended the necessity of promoting the idea of ​​applying learning styles to the third-grade teachers in distance learning for mathematics especially in teaching multiplication and division tables for their importance in all educational stages.
Keywords: learning styles; distance learning; multiplication and division; third-grade